A novel compression-assisted energy storage heat transformer for low-grade renewable energy utilization. (15th January 2023) - Ding, Zhixiong; Wu, Wei; Huang, Si-Min; Huang, Hongyu; Bai, Yu; He, Zhaohong
Abstract: Thermal energy storage is a promising method to balance the timing mismatch between the intermittent energy sources and time-variable user loads but cannot address the low-grade issue, which results in the underutilization of low-temperature renewable energy. An absorption-based energy storage heat transformer (ESHT) can achieve temperature upgrading with satisfactory storage performance. To further improve the system performance, a novel compression-assisted ESHT (CESHT) is proposed. The dynamic characteristics of the basic ESHT and CESHT cycles are analyzed and compared. Then, the effects of heat output, heat input, and heat sink temperatures on the cycle performance are investigated. Results show that significant enhancements are achieved by the CESHT cycle for both energy storage performance and temperature upgrading ability. With auxiliary compression, the temperature lift is increased from 30 °C to 65 °C, and the required input temperature is decreased from 60 °C to 45 °C. Moreover, the performance indexes are greatly improved, e.g., the energy storage efficiency, energy storage density, and exergy efficiency are respectively increased from 0.24 to 0.43, from 35.2 kWh/m 3 to 282.7 kWh/m 3, and from 0.32 to 0.54 with a temperature lift of 30 °C. The proposed cycle demonstrates the advantages of enhanced storage performance and large temperature lift.